2008
DOI: 10.1071/sr07042
|View full text |Cite
|
Sign up to set email alerts
|

Pedotransfer functions for predicting the hydraulic properties of Indian soils

Abstract: Most of the data pertaining to Indian soils are limited to the major soil separates, sand, silt, and clay. We examined the possibilities of using these parameters to describe the hydraulic characteristics of the soils of India. The final or steady-state infiltration rate, which is mainly profile-controlled, showed a power function relationship with the maximum and the average clay content in the soil profile. The saturated hydraulic conductivity also showed a similar relationship with the silt + clay content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…At −33 kPa, the PTF described in Botula et al (), using sand content, was the most accurate equation to predict volumetric water content; it overestimated the water content by less than 1%. The PTFs described in Adhikary et al (), using sand and silt contents, and Martínez‐Zavala and Jordán‐López (), using sand and clay contents, underestimated the water content by about 1.5%. At −1500 kPa, the PTF described in Aina and Periaswamy () with clay content only, overestimated the water content by less than 1%.…”
Section: Discussionmentioning
confidence: 89%
“…At −33 kPa, the PTF described in Botula et al (), using sand content, was the most accurate equation to predict volumetric water content; it overestimated the water content by less than 1%. The PTFs described in Adhikary et al (), using sand and silt contents, and Martínez‐Zavala and Jordán‐López (), using sand and clay contents, underestimated the water content by about 1.5%. At −1500 kPa, the PTF described in Aina and Periaswamy () with clay content only, overestimated the water content by less than 1%.…”
Section: Discussionmentioning
confidence: 89%
“…In general, scatterplots in Figure 3 show large biases in all directions for SWR at -10 kPa predicted by selected PTFs of Pidgeon (1972), Lal (1979) and Adhikary et al (2008) as the first group, and of van den Berg et al (1997) and Minasny and Hartemink (2011) as the second group. However, the second group has better prediction results compared to the first group, in particular the prediction result of the PTF of Minasny and Hartemink (2011), which is confirmed by the statistical indices in Table 7.…”
Section: Point Ptfsmentioning
confidence: 99%
“…al. (1987) in Tomasella and Hodnett (2004)); Dij: (Dijkerman, 1988);vdB: (van den Berg et al, 1997);Oli: (Oliveira et al (2002) in Tomasella and Hodnett (2004)); Ad: (Adhikary et al, 2008); MH: (Minasny and Hartemink, 2011); Bot: (Botula, 2013). …”
Section: Continuous Ptfsmentioning
confidence: 99%
“…The pedotransfer function for predicting the hydraulic properties of soils in India was determined by Adhikary et al (2008), who reported a decrease in infiltration rate with an increase in clay content. Mamedov et al (2001) also recorded the relationship between soil salinity, texture, infiltration, and runoff for soils in Israel.…”
Section: Soil Propertiesmentioning
confidence: 99%